1993
DOI: 10.1111/j.1471-4159.1993.tb03532.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐and Postmortem Influences on Brain RNA

Abstract: Many potentially valuable techniques for the understanding of human neurobiological and neuropathological processes require the use of RNA obtained from postmortem tissue. As with earlier neurochemical studies, there are two particular problems posed by such tissue in comparison with tissue from experimental animals. These are the postmortem interval and the condition of the patient prior to death, referred to as the agonal state. We review the nature and extent of the effects of postmortem interval and agonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
1
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(156 citation statements)
references
References 87 publications
(80 reference statements)
8
145
1
2
Order By: Relevance
“…Thus, it cannot be assumed that because one particular protein, mRNA, etc is stable, all are stable during a certain PMI. In addition to PMI and storage temperature, other factors such as agonal state at death (Bowen et al, 1976;Butterworth et al, 1983;Harrison et al, 1991;Lewis and Akil, 1997;Perry et al, 1977aPerry et al, , 1982Spokes, 1979;Yates et al, 1990), pH (generally related to agonal state) (Barton et al, 1993;Eastwood and Harrison, 2000;Harrison et al, 1995;Johnston et al, 1997;Kingsbury et al, 1995), freezing time (Roytta et al, 1980), and time or season of death (Bucht et al, 1981;Carlsson et al, 1980; Perry et al, 1977a-d), among many others, have been found to influence the degradationFor levelFof biological products in postmortem brain specimens. Thus, it remains critical to ascertain the post-mortem stability, and the stability under other conditions, of the biological product.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it cannot be assumed that because one particular protein, mRNA, etc is stable, all are stable during a certain PMI. In addition to PMI and storage temperature, other factors such as agonal state at death (Bowen et al, 1976;Butterworth et al, 1983;Harrison et al, 1991;Lewis and Akil, 1997;Perry et al, 1977aPerry et al, , 1982Spokes, 1979;Yates et al, 1990), pH (generally related to agonal state) (Barton et al, 1993;Eastwood and Harrison, 2000;Harrison et al, 1995;Johnston et al, 1997;Kingsbury et al, 1995), freezing time (Roytta et al, 1980), and time or season of death (Bucht et al, 1981;Carlsson et al, 1980; Perry et al, 1977a-d), among many others, have been found to influence the degradationFor levelFof biological products in postmortem brain specimens. Thus, it remains critical to ascertain the post-mortem stability, and the stability under other conditions, of the biological product.…”
Section: Discussionmentioning
confidence: 99%
“…However, when performing such analyses, several factors should be taken into account. Firstly, mRNA degradation after death can lead to the fragmentation of RNA species (Barton et al, 1993;Leonard et al, 1993). The longer the time spent by the corpses at high outdoor temperatures, the more severe mRNA degradation is.…”
Section: Altered Expression Of L-opioid Receptors In the Brains Of Sumentioning
confidence: 99%
“…We have taken several of these newer measures of tissue quality and tested them in human postmortem tissue in a variety of situations to detect the relationship of the markers to the real quality of the postmortem tissue. Traditionally, a low postmortem interval (Barton et al, 1993;Ferrer-Alcon et al, 2003;Harrison et al, 1995;Lewis, 2002;Trotter et al, 2002) has been the hallmark of high tissue quality. More recently tissue pH (Hynd et al, 2003;Kingsbury et al, 1995;Li et al, 2004) has been used, and even more recently, specific markers of RNA quality have been introduced (Imbeaud et al, 2005;Johnston et al, 1997;Miller et al, 2004).…”
Section: Introductionmentioning
confidence: 99%